El reino de uno mismo : la resignificación espiritual de la mirada y el espacio en Jane Eyre (2020)
In Jane Eyre, by Charlotte Bronté the construction of identity operates as a movement that impetuously intercepts the evolution of confined spaces and the social, family, and institutional configurations that inhabit them. In the narrow corridors, the closed rooms and the contained structure of the country houses, the powerful presence of social determinations that are difficult to escape and of prisons of an unbearable personal weight always appears. The representation of a world that, ultimately, is forged in symbolic labyrinths and cultural and psychological inscriptions that drag individual configurations in violently drawn circles. Given this, this work proposes that only on the fringes of such a conflicted world can personal spiritualities emerge as vanishing points and as sanctuaries of imperfect freedom. As spaces that counteract, rewrite, and reconfigure the realities of the confinement, serving as platforms for the gaze to dream...